A New Enterobacter cloacae Bacteriophage EC151 Encodes the Deazaguanine DNA Modification Pathway and Represents a New Genus within the Siphoviridae Family - Morozova, Vera; Jdeed, Ghadeer; Kozlova, Yuliya; Babkin, Igor; Tikunov, Artem; Tikunova, Nina (Viruses, 2021)
A novel Enterobacter cloacae phage, EC151, was isolated and characterized. Electron microscopy revealed that EC151 has a siphovirus-like virion morphology. The EC151 nucleotide sequence shows limited similarity to other phage genomes deposited in the NCBI GenBank database. The size of the EC151 genome is 60,753 bp and contains 58 putative genes. Thirty-nine of them encode proteins of predicted function, 18 are defined as hypothetical proteins, and one ORF identifies as the tRNA-Ser-GCT-encoding gene. Six ORFs were predicted to be members of the deazaguanine DNA modification pathway, including the preQ0 transporter. Comparative proteomic phylogenetic analysis revealed that phage EC151 represents a distinct branch within a group of sequences containing clades formed by members of the Seuratvirus, Nonagvirus, and Vidquintavirus genera. In addition, the EC151 genome showed gene synteny typical of the Seuratvirus, Nonagvirus, and Nipunavirus phages. The average genetic distances of EC151/Seuratvirus, EC151/Nonagvirus, and EC151/Vidquintavirus are approximately equal to those between the Seuratvirus, Nonagvirus, and Vidquintavirus genera (~0.7 substitutions per site). Therefore, EC151 may represent a novel genus within the Siphoviridae family. The origin of the deazaguanine DNA modification pathway in the EC151 genome can be traced to Escherichia phages from the Seuratvirus genus.